Simulation-based investigations of geometrical design effects on the efficiency of the intake manifold of a six-cylinder diesel engine. (November 2022) - Apaydin, Sule; Doner, Nimeti
Highlights: The intake manifold of a six-cylinder diesel engine is analysed. The shapes and diameters of the intake manifold are evaluated using CFD. The plenum geometry and the turning radii of the runners are determined for optimum design. The pressure, velocity distributions, and pressure loss are determined based on geometries. The lowest pressure loss and better homogeneous velocity distributions are determined. Abstract: Design studies of heavy-duty diesel engines are very important due to the high cost of production and the difficulties of experimental performance tests. This paper deals with finding the optimum geometric design parameters of the intake manifold of a locomotive diesel engine using the Computational Fluid Dynamics (CFD) methods and designing a suitable model. The designed models with different shapes and diameters are compared with the existing intake manifold in terms of pressure, velocity distributions, and pressure loss. Since the location of the intake manifold on the engine is limited, the pressure and the velocity distributions of the models are evaluated when changing the diameters and geometries of intake manifolds of the same lengths. These modifications of the manifold (shapes and diameters) are made by arranging them to fit in the engine packaging space. After the plenum geometry is determined based on the analyses of the five models, the models are also analysed for different turning radii (45 mm, 50 mm, 65 mm) of the runners at the entrance to the combustion chamber. As a result of all the analyses, the model that obtained the lowest pressure loss and best homogeneous velocity distributions is determined as the optimum design.